2019
DOI: 10.1002/jlcr.3794
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐based radiocarbon detection in the laboratory: How soon?

Abstract: Research over the past 25 years and the use of accelerator mass spectrometry (AMS) have demonstrated benefits of single‐atom counting of 14C compared with scintillation monitoring of 14C radioactive decay for a multitude of applications in drug development studies. These include pharmacokinetics and metabolism studies, microdosing studies, and quantification of DNA adducts. In the last decade, the possibility of single‐atom counting using lasers has been demonstrated, providing the possibility of simplified la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…This method works with a fixed frequency stabilized 14 CO 2 laser and combines four different techniques previously studied: laser assisted ratio analyzer (LARA), optogalvanic spectroscopy, optical impedance spectroscopy and laser intracavity absorption spectroscopy . A later study was able to replicate these initial results and resolve issues found by other authors around the repeatability of the results and the absorption background due to 13 CO 2 and 12 CO 2 . , It was demonstrated that a precision of 1% is achievable by ICOGS with a few minutes of analysis, although calibration can be challenging . The main advantage of SCAR, CRDS, and ICOGS optical techniques for 14 C detection is the possibility of real-time analysis.…”
Section: Advanced Methods For Tracking Biogenic Carbonmentioning
confidence: 94%
See 2 more Smart Citations
“…This method works with a fixed frequency stabilized 14 CO 2 laser and combines four different techniques previously studied: laser assisted ratio analyzer (LARA), optogalvanic spectroscopy, optical impedance spectroscopy and laser intracavity absorption spectroscopy . A later study was able to replicate these initial results and resolve issues found by other authors around the repeatability of the results and the absorption background due to 13 CO 2 and 12 CO 2 . , It was demonstrated that a precision of 1% is achievable by ICOGS with a few minutes of analysis, although calibration can be challenging . The main advantage of SCAR, CRDS, and ICOGS optical techniques for 14 C detection is the possibility of real-time analysis.…”
Section: Advanced Methods For Tracking Biogenic Carbonmentioning
confidence: 94%
“…Optical and laser techniques for 14 C detection and quantification have been proposed as advanced methods for measuring biogenic carbon. 104,105 Optical detection of carbon isotopes, such as 14 C, has shown some issues, especially when high precision and low limits of detection are required. A limitation being susceptibility of spectroscopic detectors to physical interference from background signals, thus, requiring chemical or physical sample preparation to improve precision.…”
Section: ■ Coprocessing In Refinery Unitsmentioning
confidence: 99%
See 1 more Smart Citation